Bilateral spontaneous dislocation of posterior chamber intraocular lens in a patient with gyrate atrophy - Kinori, Michael (Medknow Publications & Media Pvt Ltd, 2012)
We report a patient with gyrate atrophy, a rare metabolic disease, who had bilateral late spontaneous posterior dislocation of in-the-bag posterior chamber intraocular lens (PCIOL). He underwent pars plana vitrectomy, PCIOL retrieval and anterior chamber intraocular lens implantation in both eyes. This report may imply that patients with gyrate atrophy are at risk for spontaneous dislocation of intraocular lenses.